Artesunate drug-loaded 2D nano-shuttle landing on RBCs infected with malaria parasites. (2nd September 2022) - Kim, Ji-Yeong; Shin, Hyun-Il; Lee, Sang-Eun; Piao, Huiyan; Rejinold, N. Sanoj; Choi, Goeun; Choy, Jin-Ho
Abstract : 2D NPs could play a role as a nano-shuttle to deliver an AS − drug to the red blood cells (RBCs) infected with malaria parasites. Abstract : Artesunic acid (AS 0 ), a derivative of artemisinin, is recommended for the treatment of severe and complicated malaria, but its use is limited because of limitations such as a short half-life, non-specific targeting capability, low bioavailability, etc . To overcome these issues, a novel 2D inorganic delivery shuttle system for an AS 0 drug to target the malarial host, red blood cells (RBCs), is explored by immobilizing AS 0 into 2D metal hydroxides to form AS − (artesunate, the deprotonated form of artesunic acid) nanohybrid drugs. Haemolysis assay showed that the AS − nanohybrids not only are haemo-compatible but also target RBCs due to the electrostatic interaction and hydrogen bonding between RBCs and AS − nanohybrids. As clearly demonstrated by the subsequent parasite lactate dehydrogenase assay, the antimalarial effect of the AS − nanohybrids is determined to be 6 times more effective than that of intact AS 0 against malaria. Therefore, the AS − nanohybrids with haemo-compatible 2D inorganic carriers could be the promising drug delivery systems for targeting the malarial host, RBCs.